Perancangan Karakter Maskot Digital PKBM Sebaya Siduarjo:Pendekatan Visual Dalam Konteks Media Sosial Interaktif: Desain Komunikasi Visual - Bilqis Agneza Herwanda; Masnuna Masnuna; Febi Arifianto, Pungky (Jurnal Publikasi Ilmu Komputer dan Multimedia, 2025)
This study aims to Increase brand awareness through mascot design as a visual identity of PKBM Sebaya, Create a distinctive character that is able to represent the vision and mission of PKBM Sebaya Sidoarjo, Build a unique, professional and attractive impression to be recognized by customers, Help make it easier for customers to remember PKBM Sebaya through the appeal of the mascot in social media content. The research method used is qualitative descriptive analysis. Data collection techniques used in this study include interview methods, direct observation and questionnaires that are distributed directly to respondents through social media, the questionnaire used is a Google form formula. The data analysis technique used in this study is a qualitative descriptive analysis of the TOWN Matrix which is used for the results of PKBM observations. The results of the study indicate that the design of the mascot for PKBM Sebaya Sidoarjo aims to strengthen visual identity and increase the appeal of social media content, which has become less attractive. This mascot is expected to be able to increase public awareness of PKBM Sebaya. The design process is carried out through qualitative and quantitative data collection, analyzed using the TOWS Matrix approach to determine the right strategy. The main media of design are character design and mascot dolls, supported by various promotional media such as graphic standard manuals, t-shirts, x-banners, and others. This strategy is expected to significantly increase the appeal and public awareness of PKBM Pebaya